PENGARUH BRAND IMAGE DAN PROMOSI TERHADAP KEPUTUSAN PENGGUNAAN E – WALLET (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2021)
This study aims to determine the effect of brand image and promotion on the decision to use e-wallet in Dr. university students. Soetomo Surabaya both simultaneously and partially and to find out the dominant variables in the decision to use e-wallet. This research is a quantitative research with causal research method. The population in this study were all university students of Dr. Soetomo who has an application and has made transactions using e-mail, the number of samples is 96 respondents who have been distributed through questionnaires. This study uses a random sampling technique to collect respondents and uses the formula of unknown populations in determining the sample because the population in this study is unknown. Furthermore, data analysis using instrument test, classical assumption test, multiple linear regression analysis test, simultaneous test, partial test, and coefficient of determination test. The results of this study indicate that brand image and promotion have an effect either simultaneously or partially on the decision to use e-wallet and promotion is the dominant variable influencing the decision to use e-wallet.